2018
DOI: 10.1038/s41598-018-30873-0
|View full text |Cite
|
Sign up to set email alerts
|

Physiological characterization of the emergence from diapause: A transcriptomics approach

Abstract: Organisms inhabiting high-latitude environments have evolved adaptations, such as diapause to time reproduction and growth to optimize their survival. However, the physiological regulation of the timing of complex life histories is poorly understood, particularly for marine copepods, that diapause at depth. A member of the pelagic community of the sub-Arctic Pacific Ocean, Neocalanus flemingeri enters diapause in June. Egg production occurs in winter/spring. In order to characterize the transition from diapaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 62 publications
(103 reference statements)
5
48
0
Order By: Relevance
“…1,000 differentially expressed genes involved in reproduction, the progression through oogenesis is nearly synchronous in females collected in September from deep water (400 to 700 m) and incubated in the laboratory at 5 • C. The reproductive program starts with the up-regulation of genes involved in germline development, the first stage of oogenesis (OS0), and it takes 6-7 weeks before females start to spawn. While in most calanoid copepods all five stages of oogenesis are concurrent, Roncalli et al (2018b) found oogenesis to be sequential in N. flemingeri with processes associated with early oogenesis becoming down-regulated as females neared spawning.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…1,000 differentially expressed genes involved in reproduction, the progression through oogenesis is nearly synchronous in females collected in September from deep water (400 to 700 m) and incubated in the laboratory at 5 • C. The reproductive program starts with the up-regulation of genes involved in germline development, the first stage of oogenesis (OS0), and it takes 6-7 weeks before females start to spawn. While in most calanoid copepods all five stages of oogenesis are concurrent, Roncalli et al (2018b) found oogenesis to be sequential in N. flemingeri with processes associated with early oogenesis becoming down-regulated as females neared spawning.…”
Section: Introductionmentioning
confidence: 77%
“…The time series included weekly or semi-weekly sampling of deep-collected females followed by laboratory incubations starting at collection (Wk0) to 9.5 weeks post-collection (Wk9.5). In a previous study, the data from Wk0 to Wk7 were analyzed to characterize the reproductive program (Roncalli et al, 2018b).…”
Section: Neocalanus Flemingeri Rna-seq Datasetmentioning
confidence: 99%
See 3 more Smart Citations